2018
DOI: 10.1186/s12891-018-2364-4
|View full text |Cite
|
Sign up to set email alerts
|

Patient demographics and MRI-based measurements predict redundant nerve roots in lumbar spinal stenosis: a retrospective database cohort comparison

Abstract: BackgroundUp to 40% of patients diagnosed with lumbar spinal stenosis (LSS) show evidence of redundant nerve roots (RNR) of the cauda equina on their magnetic resonance images (MRI). The etiology of RNR is still unclear. Preoperative evidence of RNR is associated with a worse postsurgical outcome. Consequently, potential predictors of RNR could have a prognostic value. The aim was to test whether patient demographics and MRI-based measurements can predict RNR in LSS patients.MethodsIn a retrospective database-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 19 publications
0
8
2
Order By: Relevance
“…In patients with multilevel canal stenosis, the redundancy was noted to be above the most cranial stenotic level, this might be explained by the fact that the nerve roots are fixed between 2 points: the conus medullaris and intraforaminal ganglia and by the stensois caudally causing them to move within a tight container and thus causing them to become redundant. In our study, there was no significant statistical correlation between the multiplicity and degree of stenosis and the occurrence of RNRs opposed to the study conducted by Papavero et al 19 In our study, the presence of degenerative changes was attributed as being the cause of LCS; these changes were observed to be mainly DDB with LFH in 94% of our patients while 41.1% of them suffered from an additional change, FJH, and 6.4% had associated spondylolisthesis. Our findings support the proposition of Hur et al that suggests that LFH rather than isolated intervertebral disc bulges is the major contributing factor to spinal canal stenosis that causes mechanical stress on the nerve roots, eventually leading to their redundancy.…”
Section: Discussioncontrasting
confidence: 92%
“…In patients with multilevel canal stenosis, the redundancy was noted to be above the most cranial stenotic level, this might be explained by the fact that the nerve roots are fixed between 2 points: the conus medullaris and intraforaminal ganglia and by the stensois caudally causing them to move within a tight container and thus causing them to become redundant. In our study, there was no significant statistical correlation between the multiplicity and degree of stenosis and the occurrence of RNRs opposed to the study conducted by Papavero et al 19 In our study, the presence of degenerative changes was attributed as being the cause of LCS; these changes were observed to be mainly DDB with LFH in 94% of our patients while 41.1% of them suffered from an additional change, FJH, and 6.4% had associated spondylolisthesis. Our findings support the proposition of Hur et al that suggests that LFH rather than isolated intervertebral disc bulges is the major contributing factor to spinal canal stenosis that causes mechanical stress on the nerve roots, eventually leading to their redundancy.…”
Section: Discussioncontrasting
confidence: 92%
“…Moreover, after decompression surgery, patients with RNRs showed worse clinical scores and lower recovery rates than those without RNRs [9]. A study on potential RNR predictors demonstrated that patients with LSS with evidence of RNRs on the preoperative MRI were older had a shorter lumbar spine canal, displayed stenosis at more levels, and had more severe stenosis, compared to patients without RNRs [10]. Yokoyama et al studied patients with LSS and found that most RNRs resolved postoperatively, but some did not.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of RNRs dropped from 80% during standing to 16.7% during flexed sitting. The role of DCSA as the strongest predictor of RNRs [12] was confirmed.…”
Section: Discussionmentioning
confidence: 72%
“…In a study on potential predictors of RNRs in patients with LSS, several factors were identified as significant predictors [12]. The strongest predictors were LSS grade D and C according to Schizas [13], the number of stenotic levels involved and a decrease in the relative length of the lumbar spine.…”
Section: Introductionmentioning
confidence: 99%